Enhanced YOLOv5s + DeepSORT method for highway vehicle speed detection and multi-sensor verification - Luo, Zhongbin; Bi, Yanqiu; Yang, Xun; Li, Yong; Yu, Shanchuan; Wu, Mengjun; Ye, Qing (Frontiers in Physics, 2024)
Addressing the need for vehicle speed measurement in traffic surveillance, this study introduces an enhanced scheme combining YOLOv5s detection with Deep SORT tracking. Tailored to the characteristics of highway traffic and vehicle features, the dataset data augmentation process was initially optimized. To improve the detector's recognition capabilities, the Swin Transformer Block module was incorporated, enhancing the model's ability to capture local regions of interest. 𝐶𝐶𝐶𝐶𝐶𝐶𝐶𝐶 loss was employed as the loss function for the vehicle detection network, accelerating model convergence and achieving higher regression accuracy. The Mish activation function was utilized to reduce computational overhead and enhance convergence speed. The structure of the Deep SORT appearance feature extraction network was modified, and it was retrained on a vehicle reidentification dataset to mitigate identity switches due to obstructions. Subsequently, using known references in the image such as lane markers and contour labels, the transformation from image pixel coordinates to actual coordinates was accomplished. Finally, vehicle speed was measured by computing the average of instantaneous speeds across multiple frames. Through radar and video Multi-Sensor Verification, the experimental results show that the mean Average Precision (mAP) for target detection consistently exceeds 90%. The effective measurement distance for speed measurement is around 140m, with the absolute speed error generally within 1~8 km/h, meeting the